IMPORTANCE OF PHYSICAL CULTURE IN THE SYSTEM OF EDUCATION OF A HEALTHY LIFESTYLE. - Макарова, Елена; Касымов, Султан; Шарипова, Гульнара (SWorldJournal, 2020)
This article examines the factors of a healthy lifestyle, the concept of a healthy lifestyle, the preconditions for a normal level of physical fitness and a healthy lifestyle of students, the role of physical exercises in the formation of a healthy lifest